2012
DOI: 10.1002/anie.201201902
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Droplet Vaporization and Propulsion of Perfluorocarbon‐Loaded Microbullets for Targeted Tissue Penetration and Deformation

Abstract: Acoustic droplet vaporization of perfluorocarbon-loaded microbullets triggered by an ultrasound pulse provides the necessary force to penetrate, cleave, and deform cellular tissue for potential targeted drug delivery and precision nanosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
272
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(275 citation statements)
references
References 43 publications
3
272
0
Order By: Relevance
“…A new concept of MDV using a.c. magnetic field as the triggering source for cancer theranostics can effectively overcome the drawbacks of traditional ADV and ODV because there is no gas/bone influence of ultrasound or penetration depth limitations of a laser. [18][19][20]44,45 The stimuli-responsive vaporization process to produce microbubbles can substantially enhance ultrasound imaging, which can be further used for ultrasonography-guided magnetic hyperthermia of cancer. Importantly, the trigger by the a.c. magnetic field does not damage normal tissues where only small amount of PFH-HIONs are present.…”
Section: In Vitro and In Vivo Magnetic Field-responsive Ultrasound Immentioning
confidence: 99%
See 1 more Smart Citation
“…A new concept of MDV using a.c. magnetic field as the triggering source for cancer theranostics can effectively overcome the drawbacks of traditional ADV and ODV because there is no gas/bone influence of ultrasound or penetration depth limitations of a laser. [18][19][20]44,45 The stimuli-responsive vaporization process to produce microbubbles can substantially enhance ultrasound imaging, which can be further used for ultrasonography-guided magnetic hyperthermia of cancer. Importantly, the trigger by the a.c. magnetic field does not damage normal tissues where only small amount of PFH-HIONs are present.…”
Section: In Vitro and In Vivo Magnetic Field-responsive Ultrasound Immentioning
confidence: 99%
“…Typically, ADV employs acoustic waves to evaporate the liquid droplets. [18][19][20] However, because ultrasound is easily and substantially influenced by gas or bone, the use of ADV is restricted in vascular imaging, cancer detection and drug delivery. ODV uses a laser as the excitation source to induce the vaporization of liquid droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Under ultrasonic irradiation, the PFC droplets are vaporized, leading to the net motion of microbullets towards lamb kidney tissue. Propulsion can be modulated by adjusting external parameters like acoustic pressure, pulse duration or surfactant concentration [131].…”
Section: Ultrasonically-driven Motionmentioning
confidence: 99%
“…Another external energy source for tubular micromotors is ultrasound. Kagan et al [59] demonstrated that acoustic droplet vaporization can lead to the displacement of perfluorocarbon-loaded microtubes for targeted tissue penetration and deformation.…”
Section: External Stimulimentioning
confidence: 99%